The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1037/men0000047
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in cisgender psychologists’ and trainees’ attitudes toward transgender people.

Abstract: Research that has explored the attitudes of cisgender people toward transgender people has identified gender differences, with cisgender men commonly reporting more negative attitudes than cisgender women. However, little research has explored whether such differences exist among mental health professionals. This brief report outlines findings from 3 studies focusing on attitudes toward transgender people among 3 samples of Australian cisgender psychologists or psychology trainees. The first explored attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 19 publications
1
10
1
1
Order By: Relevance
“…However, the findings suggest that women had more positive attitudes when compared with men. This echoes findings reported in previous research on the attitudes of school staff (Riggs & Bartholomaeus, 2015;Bowers et al, 2015;Silveira & Goff, 2016), psychologists and psychology students (Riggs & Sion, 2016), and the general population (e.g. Nagoshi et al, 2008;Norton and Herek, 2013) towards trans and gender diverse people, in which men have been found to have a greater investment in, and anxiety about, the gender order and their place in it, which it has been suggested leads to more transphobic attitudes and behaviours (Riggs & Sion, 2016;Nagoshi et al, 2008;Norton and Herek, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…However, the findings suggest that women had more positive attitudes when compared with men. This echoes findings reported in previous research on the attitudes of school staff (Riggs & Bartholomaeus, 2015;Bowers et al, 2015;Silveira & Goff, 2016), psychologists and psychology students (Riggs & Sion, 2016), and the general population (e.g. Nagoshi et al, 2008;Norton and Herek, 2013) towards trans and gender diverse people, in which men have been found to have a greater investment in, and anxiety about, the gender order and their place in it, which it has been suggested leads to more transphobic attitudes and behaviours (Riggs & Sion, 2016;Nagoshi et al, 2008;Norton and Herek, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Más aún otros estudios han examinado específicamente la relación entre el fundamentalismo religioso y la transfobia mostrando resultados significativos (Fisher et al, 2017). Estos hallazgos han sido tan consistentes que se ha recomendado inclusive evaluar la religión como un predictor de actitudes negativas hacia personas Trans (Riggs & Sion, 2017).…”
Section: Discussionunclassified
“…One study found especially high rates of negative attitudes toward transgender patients among cisgender male psychologists and psychology trainees (Riggs and Sion, 2017). Additional practice guidelines (American Psychological Association, 2012Association, , 2015 call for clinicians to differentiate gender from sexual orientation, recognize effects of stigma and discrimination, appreciate various forms and meaning of biological and non-biological family and family roles, and adopt an ideological stance that LGBTQ+ status itself is neither a mental health problem nor inherently connected with mental health problems.…”
Section: Intervention With Suicidal Lgbtq+ Youthmentioning
confidence: 99%